Vagueness in Law 35 of 2009 Regarding Narcotics Abuse That Makes Overcapacity Prisons - Muhammad Meidil Putra; Miguna, Miguna Astuti (Law and Justice, 2022)
Regulations on narcotics crimes themselves have been regulated in the Narcotics Law number 35 of 2009 but still the number of narcotics abuse in Indonesia continues to increase. Although there are regulations that regulate the prohibition of drug abuse, the author is interested in researching the number of users who are sentenced to prison terms, why is rehabilitation not carried out, but more are sentenced to prison. There are several articles in the law, there is a vagueness that can be interpreted as a vagueness of different interpretations from law enforcers who have the power to impose punishment on law breakers, with the existence of this vagueness, the giving of the law is different even though in the case of which have the same resemblance. The research uses normative legal research methods. In the technique of collecting data in solving this problem, it is carried out using library research techniques, which are then analyzed qualitatively. With the form of the sound of the articles in the Narcotics Law, it can have an impact that can have a full or overcrowded impact, which is the current condition in prisons and detention centers, and results in the implementation of coaching not going well. With the updated legal form, it will provide a parser from the complexities of enforcement and enforcement of narcotics abusers.